1986
DOI: 10.1080/00049538608256422
|View full text |Cite
|
Sign up to set email alerts
|

A metacognitive curriculum to promote children's reading and learning

Abstract: This paper summarizes some of the major findings from a research project at the University of Michigan on children's reading Comprehension. The basis for the research is the observation that many young or unskilled readers do not use erective strategies to roster comprehension. The instructional studies were designed to promote children's metacognition about reading by informing them how. when and why to use various comprehension strategies. Third-and fifth-grade students received periodic instruction in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…If meta-cognitive de cits in reading regulation (and possibly knowledge about reading) are causally contributing to comprehension failure, training in such skills should improve reading comprehension. Previous studies have demonstrated that young children's knowledge about reading can be improved through instruction, but the bene ts do not readily transfer to standardized reading and comprehension tests (Paris & Jacobs, 1984;Paris, Saarnio & Cross, 1986). The lack of transfer may be taken as a sign that metacognitive skills are not that crucial for discourse-level comprehension; however training populations who have learning disabilities has met with more success (Lucangeli, Galderisi & Cornoldi, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If meta-cognitive de cits in reading regulation (and possibly knowledge about reading) are causally contributing to comprehension failure, training in such skills should improve reading comprehension. Previous studies have demonstrated that young children's knowledge about reading can be improved through instruction, but the bene ts do not readily transfer to standardized reading and comprehension tests (Paris & Jacobs, 1984;Paris, Saarnio & Cross, 1986). The lack of transfer may be taken as a sign that metacognitive skills are not that crucial for discourse-level comprehension; however training populations who have learning disabilities has met with more success (Lucangeli, Galderisi & Cornoldi, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…If the relation between knowledge and comprehension skill is found to be a direct one, it would be bene cial to teach and practise the necessary meta-cognitive skills. Meta-cognitive knowledge and skills have been successfully taught to populations of normal children (Paris & Jacobs, 1984;Paris, Saarnio & Cross, 1986) and also those with learning disabilities (Lucangeli, Galderisi & Cornoldi, 1995), but knowledge increments have been modest and experimental groups do not demonstrate superior performance on standardized assessments of comprehension (Paris & Jacobs, 1984;Paris, Saarnio & Cross, 1986). Thus it is important to establish whether the posited relation between comprehension skill and reading knowledge is a direct one.…”
mentioning
confidence: 99%
“…In the area of reading comprehension techniques involving reciprocal teaching, in which students take turns leading discussions on the meaning of text segments using activities of questioning, clarifying, summarizing and predicting, are reported by Brown and Palincsar (1982). The belief that to be effective, training in metalearning must take place over an extended period of time, lies behind studies by Paris et al (1984Paris et al ( ,1986 in which children in elementary school classes were taught for a year about strategies that are effective in reading.…”
Section: Promoting Metalearningmentioning
confidence: 99%
“…According to Paris, Saarnio, & Cross (1986), the strategies are skimming, rereading, paraphrasing, and summarizing. Ellis (1986) cited planning, checking, testing, revising and evaluation as strategies.…”
Section: Metacognitionmentioning
confidence: 99%